Technological innovations and sustainability: Shaping the future of smart cities in urban planning - Mahmood Shukur Ali, Hanan; Kareem Jalal, Sirwan; Waleed Saab, Maher; Izzat Hassan, Sharmeen; Bodnar, Nataliia; Saad Ahmed, Saif; Idris Mustafa, Salama; Abdymanap Ziiaidinovich, Pirmatov (Edelweiss Applied Science and Technology, 2024)
Smart cities have surfaced as pioneers in new urban planning practices during this era of increased urbanization rates. These advanced technologies have been implemented to improve life and solve many problems we are facing nowadays. This study seeks to investigate smart cities that can be developed in their advantages and disadvantages, as well as opportunities and threats. The main goal is to make technology more evenly accessible and utilizable within different urban neighborhoods. Our approach to analysing smart cities is multidisciplinary, including several sectors like urban planning, green city programmes, innovative urban enterprises, and information and communication technology (ICT). The study introduces eight novel models and integrates them into a comprehensive framework to assess smart cities, offering several possible applications. Findings indicate that digital technology and the Internet of Things (IoT) can significantly transform urban dynamics, per the findings. Conversely, they emphasise significant security, privacy, and economic parity concerns. The success and widespread implementation of innovative city projects will depend on how these challenges are resolved. It is imperative to tackle these issues to ensure the ongoing feasibility of intelligent cities as a viable choice for urban development. This study emphasises the need for a well-rounded approach that maximises benefits and minimises risks to promote inclusive, safe, and equitable urban environments via smart city advancements.